Phosphate solubilization potential of endophytic fungi isolated from Taxus wallichiana Zucc. roots - Adhikari, Priyanka; Pandey, Anita (Rhizosphere, 2019)
Endophytic microorganisms live inside the host plant and contribute in various biological processes, without causing any harmful effect. Inorganic phosphate solubilization, through microorganisms, is one of the major mechanisms involved in plant growth. The present study highlights the potential of endophytic fungi for their ability to solubilize insoluble phosphates in presence of tricalcium (TCP), aluminium (AlP), and iron phosphate (FeP) at different temperatures through production of phosphatases, phytases and organic acids. Five endophytic fungi, isolated from the roots of Taxus wallichiana, were identified following their phenotypic and molecular characters. Three fungal isolates showed maximum similarity with species of Penicillium (GBPI TWR_F1, GBPI TWR_F2, and GBPI TWR_F3) and two with species of Aspergillus (GBPI TWR_F4 and GBPI TWR_F5). All the endophytes solubilized phosphate by utilizing the substrates namely calcium, aluminium and iron phosphate along with the production of phosphatase and phytase enzymes. Maximum phosphate solubilization and phytase activity was recorded in case of the fungal isolate GBPI TWR_F2 (P. daleae) being 83.42 ± 3.41 µg/ml TCP, 57.63 ± 0.79 µg/ml AlP, and 57.76 ± 1.70 µg/ml FeP at 15 °C. GBPI TWR_F2 and GBPI TWR_F5 (Aspergillus sp.) produced maximum calcium phytase at 25 and 15 °C, 10.33 ± 0.13 and 10.37 ± 0.37 µM/ml, respectively. Phosphatase production was higher in acidic conditions in comparison to alkaline. In quantification of organic acids through HPLC, malic and succinic acids were determined in maximum quantity 0.97 ± 0.003 and 0.92 ± 0.008 µg/ml, respectively, followed by oxalic (0.71 ± 0.006 µg/ml) and lactic acid (0.61 ± 0.005 µg/ml). Citric acid was estimated in minimum quantity. [Display omitted]